LAMA PENYIMPANAN DAN PERBEDAAN KONSENTRASI ZPT ATONIK TERHADAP PROSENTASE TUNAS TUMBUH TEBU Var. BULULAWANG YANG BERSUMBER DARI BUD SET. - Pitaloka, Dyah; Halimah, Nur; zainal abidin (Fakultas Sains dan Teknologi, 2022)
Vigor and healthy sugarcane seeds determine the health and percentage of plant life when transferred to the field. Sugarcane (Sacharum officinarum L.) is a graminae plant whose stems are used as the main raw material for sugar. Sugar self-sufficiency is still a big challenge because there are still sugarcane problems, including the availability of seeds, seed quality. This study aims to determine the effect and interaction between storage time and differences in the concentration of Atonic PGR on the percentage of shoots growing in sugarcane seeds Var. Bululawang. This research was conducted at the Sendang Sari Ngajum screen house from May to July 2021. The design used Factorial RAK consisting of 2 factors, duration of storage differences (P), control (P0), 3 days (P1), 6 days (P2) , and 9 days and Atonic Concentration (A) namely Control (A0), A1 (3 ml/L), A2 (6 ml /L) . The data obtained were analyzed using Dsaastat and if there was a significant difference, it was continued with the 5% BNJ test. The results of the analysis showed that the application of atonic PGR and storage time had a significant effect on the percentage of shoots growing only at the beginning of growth, namely until the age of 2 WAP, while at the age of 4 to 6 WAP there was no significant difference with the treatment applied.